Effects of ‘STOP’ Mindfulness on Decreasing Cortisol in Primigravida Mothers - Anggorowati, Anggorowati; Munawaroh, Siti; Dwidiyanti, Meidiana (Jurusan Keperawatan FIKES UNSOED, 2019)
Background: Stress in pregnant women may give different effects on the development of pregnancy. Mindfulness is an intervention which can be practiced independently by primigravida mothers for stress management. Stress is indicated by a biological parameter of cortisol levels. Purpose: This study aimed to analyze the effects of mindfulness on decreasing cortisol levels in primigravida mothers. Methods: This study used a pretest-posttest quasy experimental design with a control group. The samples were 30 primigravida mothers who experienced stress in the area of public health centers in Semarang city. A consecutive sampling technique was used to select the samples. Mindfulness with STOP technique (Stop-Take a breath-Observe-Proceed) was given for four meetings for 60 minutes each. Before and after the implementation of mindfulness, 3 ml of blood was taken from the samples for the cortisol examination. Data were analyzed using a paired t-test.Results: The results showed that the majority of women (46.7%) were in the second trimester of pregnancy, and aged 20-35 years old (86.7%). The mean of cortisol level before and after the intervention was 180.60 and 152.50, respectively. There was a decrease in the level of cortisol after the implementation of mindfulness with a p-value of 0.000 (? <0.05).Conclusion: Mindfulness is effective in decreasing cortisol levels in primigravida mothers. Mindfulness can be used as an intervention to increase the self-reliance of pregnant women for stress management.